Native Herbivores Improve Sexual Propagation of Threatened Staghorn Coral Acropora cervicornis - Henry, Joseph A.; O’Neil, Keri L.; Patterson, Joshua T. (Frontiers in Marine Science, 2019)
Staghorn coral Acropora cervicornis was once spatially dominant on Caribbean reefs but is now threatened throughout its range. In recent years, advancements in ex-situ sexual propagation of Caribbean corals have increased the viability of this management strategy. Thus, improving culture methods for sexually propagated corals is important to bolster the overall coral restoration portfolio and increase genetic diversity in restored populations. In both natural systems and culture scenarios, algae proliferation negatively impacts coral growth and survival. Growing coral with native herbivores may represent a strategy for increased efficiency. We tested A. cervicornis recruits raised in replicate aquaria with identical densities of juvenile Lithopoma americanum or juvenile Batillaria minima snails plus a no-snail control. Each of three replicates per treatment contained tiles with similar numbers of recently settled, visually healthy, A. cervicornis. Tiles were photographed every three weeks for five months and coral growth, survivability, turf algae cover, and crustose coralline algae (CCA) cover were quantified. Labor time for cleaning was carefully recorded for each treatment. Results indicated improved growth and survival when A. cervicornis recruits were raised with either snail species in comparison to a no-herbivore control. Further, including snails decreased labor and eliminated turf algae cover. Interestingly, L. americanum significantly reduced CCA cover relative to the other treatments. We report some of the highest survival rates observed to date for sexually propagated Atlantic corals. Ultimately, results suggest that rearing sexually propagated A. cervicornis with native herbivores could improve the ability to employ these corals in reef restoration.